SINERGI PENTAHELIX MELALUI MEDIA ONLINE DALAM MEWUJUDKAN KAMPUS BERSIH NARKOBA KOTA BANDUNG - Sutrisno Sutrisno (Ilmu Komunikasi, FISIP Universitas Pasundan, 2022)
Big cities in Indonesia, including in West Java, such as Bandung, are attractive markets for both national and international drug dealers and dealers. With the condition of the rapid growth and development of drug distribution in the city of Bandung, including on campuses today, campuses are competing to create and carry out drug prevention and eradication programs, with the aim of cleaning campuses from the influence of psychotropic substances. Of course, this spirit will be carried out with a handling that combines all the potential of both the BNN, the campus/ARTIPENA, the Central and Regional Government, the Media, the Ministry of Defense, Advocates/PERADI, the police and NGOs such as GRANATE by jointly coordinating and develop strategies in the prevention and treatment of drug addicts both physically and psychologically, what is the most appropriate strategy in realizing a drug-free campus on campuses in the city of Bandung. Eradicating drugs is not an easy thing, it is important but requires the cooperation of many parties synergistically which is then referred to as the pentahelix synergy. The goals to be achieved include: Describing the motives of the pentahelix synergy phenomenon through online media in realizing a clean drug campus in Bandung City, Identifying Actions for the pentahelix synergy phenomenon through online media in realizing a clean drug campus in Bandung City, Identifying the Meaning of the pentahelix synergy phenomenon through social media in realizing a clean campus for drugs in the city of Bandung. The research method used is a qualitative method with a phenomenological research approach from Alfred Schutz. This study will identify what are the phenomena in the handling of drug eradication on campuses in the city of Bandung. The results of the research and discussion in this study are to produce five categories of pentahelix synergy so that the realization of a drug-free campus in the city of Bandung is as follows: Law Enforcement / Tightening of Rules, Soft skills / training on motivation, Spiritual Touch / using Islamic boarding school education or mentoring, Having a Fun Approach / Social Approach and Persuasion Through Social Media.